Firm characteristics' influence on the wealth effect of debt issue announcements in Malaysia - Ibrahim, Yusnidah; Taufil Mohd, Kamarun Nisham; Uddin, Md Mohan (Malaysia Finance Association, 2011)
This paper investigates the influence of firm characteristics which represent proxy for financial distress costs, interest tax savings, agency costs, and information asymmetry on the wealth effect of debt issue announcements. A total of 136 debt issues during the period February 2001 to October 2009 are considered in the sample of this study. Results indicate significant positive abnormal returns surrounding the debt issue announcements and that the wealth effect is influenced positively by managerial ownership but negatively influenced by asset tangibility, existing leverage and the level of free cash flows.